The Impact of Urban Sprawl on Air Quality: A Case Study of Hua-Takae Community, Latkrabang District, Bangkok, Thailand - Tanaphoom Wongbumru (Universitas Bandar Lampung (UBL), 2013)
Abstract â The purpose of this study is to investigate the impacts of urban sprawl in the Latkrabang District which directly affects to Hua-Takae Community. Effects of sprawl development were examined to understanding sprawl condition in the district. Calculating a sprawl condition in the district is equal to 33.5 of 100 that shown a low degree of sprawl. Nevertheless, Hua-Takae community are expected to be affected by urbanization and trends of growing population from various sprawl development factors including airport, industrial estates, educational center, and motorway. Lack of public transportation provision in the community by using automobile dependency that resulting air quality. The air pollution analysis based on traffic volume and population growth was found that the major sources were passenger car and pick-up and the major pollutants were CO and PM. The vehicle emissions of mobile sources in 2005, 2010, and 2015, are also found that higher emission standards. The emissions from mobile sources, therefore, it needs to be addressed the related policy for improving air quality of community in future.